Immunological Reaction in TNF-α-Mediated Osteoclast Formation and Bone Resorption In Vitro and In Vivo - Kitaura, Hideki (Hindawi Publishing Corporation, 2013)

(untitled)
Tumor necrosis factor-α (TNF-α) is a cytokine produced by monocytes, macrophages, and T cells and is induced by pathogens, endotoxins, or related substances. TNF-α may play a key role in bone metabolism and is important in inflammatory bone diseases such as rheumatoid arthritis. Cells directly involved in osteoclastogenesis include macrophages, which are osteoclast precursor cells, osteoblasts, or stromal cells. These cells express receptor activator of NF-κB ligand (RANKL) to induce osteoclastogenesis, and T cells, which secrete RANKL, promote osteoclastogenesis during inflammation. Elucidating the detailed effects of TNF-α on bone metabolism may enable the identification of therapeutic targets that can efficiently suppress bone destruction in inflammatory bone diseases. TNF-α is considered to act by directly increasing RANK expression in macrophages and by increasing RANKL in stromal cells. Inflammatory cytokines such as interleukin- (IL-) 12, IL-18, and interferon-γ (IFN-γ) strongly inhibit osteoclast formation. IL-12, IL-18, and IFN-γ induce apoptosis in bone marrow cells treated with TNF-α   in vitro, and osteoclastogenesis is inhibited by the interactions of TNF-α-induced Fas and Fas ligand induced by IL-12, IL-18, and IFN-γ. This review describes and discusses the role of cells concerned with osteoclast formation and immunological reactions in TNF-α-mediated osteoclastogenesis in vitro and in vivo.